Twelve Years after the Financial Crisis – Too-big-to-fail is still with us. Comments on the Financial Stability Board's Consultation Report 'Evaluation of the Effects of Too-big-to-fail reforms' - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2020)
The paper contains comments made on the Financial Stability Board's (FSB) Consultation Report concerning the success of regulatory reforms since the global financial crisis of 2007-2009. According to these comments, the FSB's assessment of the role of equity is too narrow, being phrased in terms of bankruptcy avoidance and risk taking incentives, without attention to debt overhang creating distortions in funding choices, as well as the systemic impact of ample equity reducing deleveraging needs after losses and equity contributing to smoothing of lending and asset purchases over time. The FSB's treatment of systemic risk pays too little attention to mutual interdependence of different parts of the system that is not well captured by linear causal relationships. Finally, the comments point out that bank resolution of systemically important institutions is still not viable, for lack of political acceptance of single-point-of-entry procedures, for lack of funding of banks in resolution (in the EI), for lack of fiscal backstops (in the EU), and for lack of political acceptance of bank resolution with bail-in.
Keywords: G01; G18; G21; G28; K23; 330; Financial Stability Board; too-big-to-fail; systemic risk; banking regulation; bank resolution